PENERAPAN MODEL PEMBELAJARAN SEARCH, SOLVE, CREATE AND SHARE (SSCS) UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KESETIMBANGAN KELARUTAN DI KELAS XI MIA SMAN 2 PEKANBARU - Andayu, Syulbi; Susilawati, Susilawati; Haryati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The research about Search, Solve, Create and Share (SSCS) learning model has been done in SMAN 2 Pekanbaru. The purpose of study is to improve learning achievement of learners on the subject of solubility equilibrium in class XI science SMAN 2 Pekanbaru. The type of research is experimental research with randomized control group pretest-posttest design. The sample of the study consisted of 2 classes, class XI MIA1 as experimental class and class XI MIA5 as the control class chosen randomly after homogeneity test. The experimental class is applied to the SSCS learning model, while the control class does not apply the SSCS learning model. The data analysis technique used is t-test. Based on the above analysis test data obtained thitung>ttabel that is 4,68 >1,66, meaning the impelementation of learning model SSCS can improve student learning achievement on the subject of solubility equilibrium in class XI science SMAN 2 Pekanbaru with category increase in learning achievement high that is 0,83.Keywords : Learning Achievement, SSCS Learning Model, Solubility Equilibrium